Current management of patients with chronic myelomonocytic leukemia. Issue 1 (January 2017) - Alfonso, Ana; Montalban-Bravo, Guillermo; Garcia-Manero, Guillermo
Abstract : Purpose of review: The present review will focus on the current management of patients with chronic myelomonocytic leukemia (CMML) as well as in future therapeutic perspectives. Recent findings: CMML is a clonal hematopoietic stem cell disorder characterized by peripheral blood monocytosis and myelodysplastic and myeloproliferative alterations in the bone marrow. Clinical behavior of the disease can be heterogeneous, with some patients having an indolent form of the disease, whereas others experience an aggressive course with decreased survival and eventual transformation to leukemia. Multiple studies have helped define the clinical, cytogenetic and mutational prognostic features of the disease. In addition, several prognostic scoring systems have been developed for patients with CMML. Incorporation of mutation data, particularly presence of frameshift and nonsense ASXL1 mutations, into these models seems to be allowing to further improve our ability to predict patient outcomes. Summary: Prognosis of patients with CMML is heterogeneous. Incorporation of mutational data into current clinical prognostic models has allowed to improve our ability to predict patient outcomes. Allogeneic stem cell transplantation remains the only potentially curative treatment for patients with CMML but is only an option for a subset of patients. For this reason, hypomethylating agents such as 5-azacitidine and decitabine have become the backbone of current therapy for patients with CMML, but new therapeutic strategies are required to improve their outcomes.